QUERCETIN, LACTOBACILLUS, VITAMIN D3 – THE GOLDEN THREE THAT WILL HELP YOU WITH YOUR ALLERGY PROBLEMS - Barbara Pękowska; Adrianna Brzozowska; Karolina Niewczas; Katarzyna Kozon; Anna Bielicka; Hubert Bochenek; Irmina Czerepak; Julia Gugulska; Michał Bzoma; Karolina Jaros; Adam Niedziela; Dominik Domoń (International Journal of Innovative Technologies in Social Science, 2025)
Objective: Allergic diseases, including asthma, atopic dermatitis (AD) and allergic rhinitis (AR), are increasingly prevalent and significantly impact quality of life. These conditions are driven by an overactive Th2 immune response, leading to chronic inflammation. There is growing interest in novel therapies, such as quercetin, Lactobacillus species and vitamin D₃, which exhibit immunomodulatory properties and could offer new therapeutic strategies for managing allergic diseases. Methods: This review explores the role of quercetin, Lactobacillus spp. and vitamin D₃ in modulating immune responses associated with asthma, atopic dermatitis and allergic rhinitis. We examined current literature on their mechanisms of action, effects on immune modulation and clinical evidence supporting their use in allergic conditions. Key findings: Quercetin demonstrated anti-inflammatory, antioxidant, and immunomodulatory effects, reducing Th2 cytokine production and mitigating inflammation in asthma, atopic dermatitis and allergic rhinitis. Lactobacillus species, especially L. rhamnosus and L. plantarum, promoted immune tolerance by enhancing regulatory T cell activity and improving gut barrier integrity. Vitamin D₃, through its active form calcitriol, attenuated Th2-driven inflammation, strengthened epithelial barriers, and improved clinical outcomes in asthma, atopic dermatitis and allergic rhinitis. Conclusions: Quercetin, Lactobacillus spp. and vitamin D₃ show promising potential as adjunctive therapies in allergic diseases. These interventions modulate key immune pathways, reduce inflammation and restore immune balance. However, further research is needed to establish optimal dosages and treatment regimens.